Commercially pure titanium implants with surfaces modified by laser beam with and without chemical deposition of apatite. Biomechanical and topographical analysis in rabbits - Queiroz, Thallita P. [UNESP]; Souza, Francisley Ávila [UNESP]; Guastaldi, Antônio C. [UNESP]; Margonar, Rogério; Garcia-Júnior, Idelmo R. [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Wiley, 2013)
Objectives: The purpose of this study was to evaluate the surfaces of commercially pure titanium (cp Ti) implants modified by laser beam (LS), without and with hydroxyapatite deposition by the biomimetic method (HAB), without (HAB) and with thermal treatment (HABT), and compare them with implants with surfaces modified by acid treatment (AS) and with machined surfaces (MS), employing topographical and biomechanics analysis. Methods: Forty-five rabbits received 75 implants. After 30, 60, and 90 days, the implants were removed by reverse torque and the surfaces were topographically analyzed. Results: At 30 days, statistically significant difference (P < 0.05) was observed among all the surfaces and the MS, between HAB/HABT and AS and between HAB and LS. At 60 days, the reverse torque of LS, HAB, HABT, and AS differed significantly from MS. At 90 days, difference was observed between HAB and MS. The microtopographic analysis revealed statistical difference between the roughness of LS, HAB, and HABT when compared with AS and MS. Conclusions: It was concluded that the implants LS, HAB, and HABT presented physicochemical and topographical properties superior to those of AS and MS and favored the osseointegration process in the shorter periods. In addition, HAB showed the best results when compared with other surfaces. © 2012 John Wiley & Sons A/S.
Keywords: Dental implantation; Durapatite; Lasers; Surface properties; Torque